Yeast Culture Collections as Infrastructures - Kaderian, Santiago Manuel (2024)
Culture collections can be interpreted as infrastructures whose role is the preservation, classification and research of microorganisms. Reference collections are cited in scientific articles and are sources of materials and information in research, development activities and in the industrial sector. This paper begins by addressing its use as a reference in scientific articles and then analyzes the problematization of collection managers in terms of the implications of the technologies associated with yeast identification and the emergence of biodiversity and ecology as themes. The conceptual axis of the article is based on the conceptualizations of infrastructure from Social Studies of Science and Technology. The article has a qualitative approach and uses document analysis, in scientific articles and handbooks, as well as consultations with researchers as a technical guide. The findings have to do with the transversal nature of the problem of insufficient data regarding ecology and other dimensions as pointed out by scientists in charge of reference collections, the emergence of biodiversity as a notion associated with international policies and global problems, and the scientific and technical effects of new identification technologies in research modalities.